2015
DOI: 10.1007/s12031-015-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin A Supplementation on FoxP3 and TGF-β Gene Expression in Avonex-Treated Multiple Sclerosis Patients

Abstract: Multiple sclerosis (MS) is an autoinflammatory condition of the central nervous system with impaired T helper (Th)17 and regulatory T cell (Treg) balance that is involved in disease immunopathogenesis. The vitamin A active metabolite, retinoic acid, can re-establish this imbalance through the modulation of gene expression of specific nuclear receptors including Forkhead box P3 (FoxP3). At present, few data exist on the impact of vitamin A supplementation on T cell balance. This study reports the results of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…Thereby, fluctuations in the numbers of both Th populations seem to be influenced by microRNA clusters, suggesting miRNAs as targets for MS treatment. Additionally, vitamin A supplementation was proposed to up‐regulate Treg markers and may therefore be suitable to reduce disease activity in patients with MS . Other therapeutic interventions shown to reduce IL‐17 and IL‐23 levels, decrease peripheral and central Th17 responses and enhance Treg frequency and IL‐10 production are promising in MS therapy.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Thereby, fluctuations in the numbers of both Th populations seem to be influenced by microRNA clusters, suggesting miRNAs as targets for MS treatment. Additionally, vitamin A supplementation was proposed to up‐regulate Treg markers and may therefore be suitable to reduce disease activity in patients with MS . Other therapeutic interventions shown to reduce IL‐17 and IL‐23 levels, decrease peripheral and central Th17 responses and enhance Treg frequency and IL‐10 production are promising in MS therapy.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Our team found that vitamin A supplementation results in downregulation of RARα and RARγ in PBMCs of MS patients (Bitarafan et al 2013). Furthermore, vitamin A supplementation significantly reduces IL-17 levels and inhibits gene expression of RORγt , reciprocally promoting TGF-β production and inducing FoxP3 expression in patients with MS (Saboor-Yaraghi et al 2015). These findings show that vitamin A plays a key role in MS immunopathogenesis and deficiency of this nutrient can contribute to progression of disease through multiple mechanisms.…”
Section: Vitamin a Deficiency And Msmentioning
confidence: 69%
“…There was also a predominance of studies (19.0%; n= 12) that assessed the role of antioxidant vitamins (A, C and/or E) in the development and/or evolution of MS [9][10][11][12][13][14][15][16][17][18][19][20] and the influence of some natural bioactive compounds, flavonoids and non-flavonoids with antioxidant and/or anti-inflammatory power (12.7%, n= 8), in the disease development, in particular in demyelination 21 control, and consequently, in the progress of symptoms such as muscular weakness and fatigue 22 .…”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 101 dietary components/nutritional patterns studied because some studies assessed more than one of these components. 56 ; Jelinek et al 52 ; Koriem 57 ; Malli et al 31 ; Masullo et al 13 ; Peterlik 58 ; Polachini et al 16 ; Romero et al 59 ; Schmitz et al 18 ; Shiri-Shahsavar et al 19 ; Torkildsen et al 20 63 ; Hoare et al 62 ; Mauriz et al 14 ; Nieto et al 15 ; Pantzaris et al 61 ; Rezapour-Firouzi et al 28 ; Rezapour-Firouzi et al 30 ; Schmitz et al 18 ; Shiri-Shahsavar et al 19 ; Timmermans et al 60 ; Weiland et al 43 Antioxidant Vitamins 12 19.0 Dorosty-Motlagh et al 9 ; Geldern; Mowry 10 ; Honarvar et al 11 ; Loken-Amsrud 12 ; Masullo et al 13 ; Mauriz et al 14 ; Nieto et al 15 ; Polachini et al 16 ; Saboor-Yaraghi et al 17 ; Schmitz et al 18 ; Shiri-Shahsavar et al 19 ; Torkildsen et al 20 Bioactive compounds 8 12. Hagan et al 35 ; Jelinek et al 36 ; Oliveira et al 37 ; Wens et al 38 .…”
Section: Resultsmentioning
confidence: 99%